The Correlation between HIV/AIDS Positive Pregnant Mother with Infant APGAR Score in RSD dr. Soebandi Jember - Nurlaila Ayu Purwaningsih; Muhammad Ali Shodikin; Cholis Abrori (Journal of Agromedicine and Medical Sciences, 2018)
Human Immunodeficiency Virus (HIV) is a virus that decreased immunity and a set symptoms of diseases called Acquired Immune Deficiency Syndrome (AIDS). One of the major risk factors for HIV transmission is perinatal transmission about 2.8% during pregnancy, delivery, and postpartum. HIV positive mothers have a potential to give birth infants with low APGAR. APGAR Score was used as a reference to determine asphyxia in the first and fifth minutes of life. The purpose of this research were to determine the correlation between HIV/AIDS positive pregnant mother with infant APGAR Score and to determine the other factors that affect the infant APGAR Score in RSD dr. Soebandi Jember. This research used observational analytic survey method with cross sectional design using medical record of HIV positive and negative pregnant women from August 2014-July 2017 in RSD dr. Soebandi Jember as a subject that qualify the inclusion and exclusion criteria. This research used case group sampling technique by total sampling and control group by simple random sampling each 52 samples. Test result of the correlation between HIV/AIDS positive pregnant mother with infant APGAR Score using Chi-Square test obtained p value=1.000 (OR=1.13) that means there was no significant correlation. Test result of the correlation between the other factors that affect infant APGAR Score concluded that there were no significant correlation. Keywords: pregnant mother, HIV/AIDS, APGAR Score, infant